2021
DOI: 10.1038/s41467-021-26257-0
|View full text |Cite|
|
Sign up to set email alerts
|

Fine cubic Cu2O nanocrystals as highly selective catalyst for propylene epoxidation with molecular oxygen

Abstract: Propylene epoxidation with O2 to propylene oxide is a very valuable reaction but remains as a long-standing challenge due to unavailable efficient catalysts with high selectivity. Herein, we successfully explore 27 nm-sized cubic Cu2O nanocrystals enclosed with {100} faces and {110} edges as a highly selective catalyst for propylene epoxidation with O2, which acquires propylene oxide selectivity of more than 80% at 90–110 °C. Propylene epoxidation with weakly-adsorbed O2 species at the {110} edge sites exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…The electrocatalytic oxidations of different small organic molecules on various edited electrodes have been examined for application in fuel cells 7 13 . Most of recent reports, polyalcohol such as ethylene glycol, propylene glycol and glycerol, are a good choice in fuel cells due to its high reactivity in electro-oxidation, inflammability, lower toxicity and high boiling point that allows tranquil handling and storage 14 , 15 . Polyalcohol fuels are valuable due to they can be produced from renewable sources 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic oxidations of different small organic molecules on various edited electrodes have been examined for application in fuel cells 7 13 . Most of recent reports, polyalcohol such as ethylene glycol, propylene glycol and glycerol, are a good choice in fuel cells due to its high reactivity in electro-oxidation, inflammability, lower toxicity and high boiling point that allows tranquil handling and storage 14 , 15 . Polyalcohol fuels are valuable due to they can be produced from renewable sources 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic nanoparticles (Cu and Ag) can also restructure and grow from illumination-induced localized heating ( Kumari et al., 2021 ), ( Molotskii, 2009 ). This can change the distribution of exposed crystal facets and ratio between terrace, kink, and edge sites, affecting selectivity ( Van Hardeveld and Hartog, 1969 ), ( Xiong et al., 2021 ). Also, the distribution and activation of specific reaction intermediates can be influenced by light through selective electronic injection into vacant adsorbate antibonding orbitals, leading to accelerated reaction rates or altered product distribution ( Figure 1 C) ( Tan et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed calculation equations followed the method proposed by Huang et al and are shown in the ESI †. 3…”
Section: Methodsmentioning
confidence: 99%
“…20 Recently, Huang et al explored ultrafine cubic Cu 2 O as a nanocatalyst, which showed propylene epoxidation selectivity of over 80% but conversion of 0.2% at 90–110 °C. 3 Xie et al further demonstrated that Cl-doped rhombic dodecahedral Cu 2 O exhibited enhanced PO selectivity of 63% and conversion of 1% at 200 °C. 21 Hutchings et al showed that 1-hexen-3-one (selectivity ∼38%) and 1-hexen-3-ol (∼25%) were the major products, with 18% 1,2-epoxyhexane, using graphite-supported Au at 50 °C (0.1 Mpa O 2 ) in the solvent-free oxidation of 1-hexene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation